Pengaruh CR & QR Terhadap ROE Pada Bank Muamalat Periode 2014 - 2023 - Muhamad Rafly Hadiansyah; Tamala Setiarini; Andri Priadi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the influence of the Current Ratio (CR) and Quick Ratio (QR) on Return on Equity (ROE) at Bank Muamalat Indonesia. CR and QR, as indicators of a company's liquidity, are expected to show the extent of their impact on the return on equity, which reflects the bank’s profitability. The research method employed is a quantitative approach using multiple linear regression analysis. The data used are secondary data obtained from the annual financial reports of Bank Muamalat for a specific period. The results show that CR has a negative but insignificant effect on ROE, while QR has a positive and significant effect on ROE. Simultaneously, CR and QR have a significant influence on ROE. These findings imply that effective liquidity management is essential to improve the bank’s profitability. This study is expected to serve as a reference for Bank Muamalat’s management in making more optimal financial decisions, as well as a consideration for investors in making investment decisions.